Multiple impacts of environmental regulation on the steel industry in China: A recursive dynamic steel industry chain CGE analysis. (10th February 2019) - Zhu, Xuehong; Zeng, Anqi; Zhong, Meirui; Huang, Jianbai; Qu, Hongping
Abstract: With the increasing international attention paid to environmental issues, the ability to pursue continuous development while protecting the environment and thereby achieving a win-win situation has become a significant issue for developing countries such as China. In previous studies, environmental regulation has been proven to be an effective governance mechanism. However, few studies have attempted to analyse the comprehensive impacts and determine the optimal stringency of environmental regulation, especially for a specific industry, based on the actual situation in China. Therefore, this paper calculates the effects of the current and proposed environmental regulation of China's steel industry from 2006 to 2013 by adopting a pollution treatment approach, and based on this calculation, it constructs a recursive dynamic steel industry chain CGE model to investigate the macroeconomic, market and technology impacts from an industry chain perspective under 3 different levels of environmental regulation of the steel industry. The simulation results show that real GDP and the outputs of the downstream sectors of the steel industry will suffer slightly, while the outputs and exports of the steel industry itself will benefit from stringent environmental regulation over the long term. In addition, the material efficiency of steel use will be improved in the long term through the implementation of environmental regulation of the steel industry. Based on the results, it is recommended that a moderate level of environmental regulation should be adopted initially, which can then be smoothly transformed into more stringent regulation during a period of economic growth to avoid sudden and major shocks. In addition, this paper also provides a reference for other substantial industries in China when choosing the optimal pattern for the implementation of environmental regulations. Highlights: The current environmental regulation of China's steel industry is far from adequate for compensating for the full external environmental costs. A recursive dynamic steel industry chain CGE model of China is constructed. The outputs and exports of China's steel industry will benefit from stringent environmental regulation. The material efficiency of steel use will be improved in the long term while not sensitive to the stringency of environmental regulation.